2019
DOI: 10.1039/c8ra10061f
|View full text |Cite
|
Sign up to set email alerts
|

Normal saline-induced deoxygenation of red blood cells probed by optical tweezers combined with the micro-Raman technique

Abstract: The use of normal saline for washing red blood cells and treating critically ill patients is a regular medical practice in hospital settings. An optical tweezer in combination with Raman spectroscopy is an analytical tool employed for the investigation of single cell dynamics, thus providing molecular fingerprint of the cell by optically trapping the cell at a laser focus. In this study, the impact of normal saline on individual human red blood cell was compared with that of blood plasma using Raman tweezers s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The oxygenation markers in the Raman spectra show prominent intensity enhancement in plasma compared with normal saline. This observation is drawn by monitoring the peaks mainly at 565; 1,222; 1,561; and 1,636 cm ‐1 . To maintain the blood oxygenation conditions and to keep the cells intact for long time, all the alcohol experiments were further continued with blood plasma as the solvent medium.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The oxygenation markers in the Raman spectra show prominent intensity enhancement in plasma compared with normal saline. This observation is drawn by monitoring the peaks mainly at 565; 1,222; 1,561; and 1,636 cm ‐1 . To maintain the blood oxygenation conditions and to keep the cells intact for long time, all the alcohol experiments were further continued with blood plasma as the solvent medium.…”
Section: Resultsmentioning
confidence: 92%
“…This observation is drawn by monitoring the peaks mainly at 565; 1,222; 1,561; and 1,636 cm -1 . [27] To maintain the blood oxygenation conditions and to keep the cells intact for long time, all the alcohol experiments were further continued with blood plasma as the solvent medium. Because the cells in plasma are showing the oxygenation trend, any stress-induced deoxygenation effect can be clearly noted from the respective established spectral regions (methine deformation region, spin marker region, pyrrole deformation region, etc.…”
Section: Resultsmentioning
confidence: 99%
“…This specific band region comprises Raman signatures that were scattered from the C-C bonds in the porphyrin ring and rely on the spin-state of the iron atom ( Wood and McNaughton, 2002 ). It is an important spectral range to explore, as it describes the “oxygenation” (oxy) state of Hb ( Lukose et al, 2019 ). The Raman peaks at 1,524, 1,545, 1,563, 1,602, 1,617, and 1,636 cm –1 exhibited a decrease in their intensities in the jaundice samples when compared to their corresponding peaks from the healthy samples.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that RBCs in the "jaundice environment" produced heme-aggregates within themselves. There appeared to be a shift in the 1,370 cm −1 (oxy state) peak to 1,375 cm −1 (deoxy state) in jaundice, ascertaining lesser oxy states in jaundice (Lukose et al, 2019).…”
Section: Rbc Raman Markers Detected In Jaundicementioning
confidence: 90%
See 1 more Smart Citation